Molecular epidemiology and antimicrobial resistance of human Streptococcus suis isolates in Guangxi, China, 2015–2021 - Xueli Yi; Bin Luo; Yuanyuan Dai; Ying Wei; Shimao Zhong; Ying Deng; Chunfang Wang; Yuanji Teng (Frontiers in Public Health, 2026)
Background Streptococcus suis ( S. suis ) is an important zoonotic pathogen and a common colonizer of the upper respiratory tract of pigs. Human infections have been reported in several regions of China, including Guangxi, but genomic and antimicrobial resistance data from this region remain limited. This study investigated the molecular epidemiology, antimicrobial susceptibility, and genomic characteristics of human S. suis isolates collected in Baise City, Guangxi, from 2015 to 2021. Methods This retrospective study included 39 non-duplicate clinical isolates confirmed as S. suis by whole-genome analysis. Antimicrobial susceptibility testing was performed using a broth microdilution-based system and interpreted according to the Clinical and Laboratory Standards Institute guidelines. Serotypes were determined by agglutination using type-specific antisera. Whole-genome sequencing was used for species confirmation, multilocus sequence typing, detection of antimicrobial resistance and virulence-associated genes, and core-protein phylogenetic analysis. Results The median patient age was 55 years, and 36/39 (92.3%) patients were male. Meningitis was documented in 34/39 (87.2%) patients, and hearing impairment occurred in 21/39 (53.8%). Pig- or pork-related exposure was recorded in 15/39 (38.5%) patients. Resistance was highest to tetracycline (38/39, 97.4%), followed by erythromycin and clindamycin (26/39, 66.7% each). Four isolates (10.3%) showed intermediate susceptibility to penicillin, but none were resistant. All isolates remained susceptible to ampicillin, ceftriaxone, levofloxacin, linezolid, vancomycin, and meropenem. Serotype 2 predominated (32/39, 82.1%), followed by serotype 14 (7/39, 17.9%), while ST1 (29/39, 74.4%) and ST7 (7/39, 17.9%) were the two major sequence types. Resistance genes were mainly associated with tetracyclines, macrolides, lincosamides, and aminoglycosides. All ST1 isolates carried mrp and lacked tet (40), while all ST7 isolates showed the reverse pattern. Conclusion Serotype 2 and ST1 predominated among the human S. suis isolates collected at this center. Resistance to tetracycline, erythromycin, and clindamycin was common, while susceptibility to the β -lactams tested was largely preserved. Differences in virulence- and resistance-associated gene profiles were also observed between the major lineages, indicating distinct genetic characteristics among the locally circulating isolates.